Stein's neuronal model with pooled renewal input - Rajdl, Kamil; Lansky, Petr (Biological cybernetics, 2015)
The input of Stein's model of a single neuron is usually described by using a Poisson process, which is assumed to represent the behaviour of spikes pooled from a large number of presynaptic spike trains. However, such a description of the input is not always appropriate as the variability cannot be separated from the intensity. Therefore, we create and study Stein's model with a more general input, a sum of equilibrium renewal processes. The mean and variance of the membrane potential are derived for this model. Using these formulas and numerical simulations, the model is analyzed to study the influence of the input variability on the properties of the membrane potential and the output spike trains. The generalized Stein's model is compared with the original Stein's model with Poissonian input using the relative difference of variances of membrane potential at steady state and the integral square error of output interspike intervals. Both of the criteria show large differences between the models for input with high variability.
Keywords: Neurons; stochastické procesy; modely neurologické; membránové potenciály; Nerve Net; zvířata; Humans; Membrane Potentials; Models, Neurological; nervová síť; Stochastic Processes; neurony; lidé; Animals